2020
DOI: 10.3390/pharmaceutics12080708
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and Advanced Cell Respiration Effects, Enhanced by Toxic Human-Bile Nano-Pharmaceuticals of Probucol Cell-Targeting Formulations

Abstract: Bile acids have recently been studied for potential applications as formulation excipients and enhancers for drug release; however, some bile acids are not suitable for this application. Unconjugated lithocholic acid (ULCA) has recently shown drug formulation-stabilizing and anti-inflammatory effects. Lipophilic drugs have poor gut absorption after an oral dose, which necessitates the administration of high doses and causes subsequent side effects. Probucol (PB) is a highly lipophilic drug with poor oral absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 84 publications
(147 reference statements)
2
17
0
Order By: Relevance
“…Calculated encapsulation efficiency of CBD was 23±1.2% and CBD loading was estimated as 2.05±0.10%. Drug loading was comparable to previous studies [ 23 ]. The encapsulation efficiency remained relatively low despite multiple optimisations.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Calculated encapsulation efficiency of CBD was 23±1.2% and CBD loading was estimated as 2.05±0.10%. Drug loading was comparable to previous studies [ 23 ]. The encapsulation efficiency remained relatively low despite multiple optimisations.…”
Section: Resultssupporting
confidence: 87%
“…The encapsulation efficiency remained relatively low despite multiple optimisations. A recent study by Wagle et al [ 23 ] that utilised a similar encapsulation protocol on probucol reported a drug loading of approximately 2% but with an encapsulation efficiency as high as 92%. The drug used in the aforementioned study was in powder form, which may have been a major determinant of the encapsulation efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Given probucol’s up-regulation of NRF2 expression, it presents a viable option for potential benefits in ARHL prevention and management [ 33 ]. Therapeutic applications of probucol have been previously shown to reduce proinflammatory cytokines TNF-α, IL-1β, IL-6, IFN-γ, and increase the anti-inflammatory cytokine IL-10 [ 83 , 91 , 92 , 93 ]. Probucol provides extremely multifaceted mechanisms of assistance in ARHL, as summarised in Figure 1 , but despite its effectiveness, probucol requires a well-developed method of drug delivery.…”
Section: Antioxidantsmentioning
confidence: 99%
“…The addition of DCA to gliclazide promoted the transport of gliclazide across the blood–brain barrier to a factor of three in healthy rats and a factor of four in diabetic rats [ 159 ]. Several studies have shown that the addition of DCA to drug carriers improves the mechanical and osmotic stability of drug carriers, improved controlled release delivery outcomes, and chemical stability with probucol addition [ 93 , 130 , 132 , 136 , 148 , 154 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 ]…”
Section: Bile Acidsmentioning
confidence: 99%
“…The secondary bile acid lithocholic acid (LCA) has shown anti-inflammatory and formulation-stabilising effects in atherosclerosis [ 23 ]. Our group studied the impact of PB-LCA microcapsules on pancreatic β-cells and found positive effects on cell viability, including anti-inflammatory effects and increased bioenergetic parameters [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%